PENGARUH PENGENDALIAN INTERNAL, KESESUAIAN KOMPENSASI, KETAATAN ATURAN AKUNTANSI, DAN KEADILAN PROSEDURAL TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (Survei pada Aparatur Pemerintah Daerah Se-Eks Karesidenan Surakarta) - Pujiastuti, Hartini; Rispantyo, Rispantyo; Kristianto, Djoko (Universitas Slamet Riyadi, 2021)
The research was conducted to measure the internal influence, suitabilityof compensation, compliance with accounting rules and procedural fairness onthe tendency of accounting fraud. This study uses primary data from the answersto the questionnaire sent to local government officials throughout the SurakartaResidency. Sampling was taken using purposive sampling method technique whichis believed to be 65 respondents. Analysis of research data is descriptivestatistical test, validity test, reliability test, classical assumptions, multiple linearregression analysis test, t test, F test and test of determination (R2). The results ofthis study are internally coordinated, the suitability of compensation, adherence toaccounting rules and procedural fairness coefficients are negative and have asignificant effect on the tendency of accounting fraud.